Big Data Analytics : Turning Big Data into Big Money - Ohlhorst, Frank J. (Hoboken : Wiley, 2012)
Unique insights to implement big data analytics and reap big returns to your bottom line Focusing on the business and financial value of big data analytics, respected technology journalist Frank J. Ohlhorst shares his insights on the newly emerging field of big data analytics in Big Data Analytics. This breakthrough book demonstrates the importance of analytics, defines the processes, highlights the tangible and intangible values and discusses how you can turn a business liability into actionable material that can be used to redefine markets, improve profits and identify new business opportuni.
In-Memory ProcessingChapter 10: Bringing It All Together; The Path to Big Data; The Realities of Thinking Big Data; Hands-on Big Data; The Big Data Pipeline in Depth; Big Data Visualization; Big Data Privacy; Appendix: Supporting Data; ""The MapR Distribution for Apache Hadoop""; ""High Availability: No Single Points of Failure""; About the Author; Index.
Print version record.
Keywords: Business intelligence; Data mining; Business intelligence; Data mining; Internet; Business intelligence; Data mining; Electronic books